Nitrogen-Doped Multi-Scale Porous Carbon for High Voltage Aqueous Supercapacitors - Liu, Xichuan; Mi, Rui; Yuan, Lei; Yang, Fan; Fu, Zhibing; Wang, Chaoyang; Tang, Yongjian (Frontiers in Chemistry, 2018)
Recently, ‘Water-in-salt’ electrolyte has been reported to extend the working voltage of aqueous supercapacitor. However, this electrolyte needs the electrode materials possess some good features such as proper pore structure, high electron and ion conductivity. Herein, we fabricated the nitrogen-doped multi-scale porous carbon (NMC) by the simple enriching melamine-resorcinol-formaldehyde xerogels method with integrating triblock copolymer for micro-pores formation. All the results confirmed that our NMC is provided with a very high specific surface area (3170 m2 g-1) and its monoliths are composed of multi-scale porous structure. By employing the nanostructured NMC as electrode materials, we have investigated the capability for high-voltage aqueous supercapacitor applications. The superconcentrated ‘Water-in-salt’ electrolyte expand stability operating potential window of aqueous symmetric supercapacitor up to 2.4 V with a high energy density of 33 Wh kg−1 at power density of 0.3 kW kg−1. Our studies indicate that the NMC is potential materials for high performance over wider voltage range.